Roadblocks faced by graphene in replacing graphite in large-scale applications. Issue 1 (8th March 2021) - Owuor, Peter Samora; Khan, Abdullah; Leon, Carlos Leon y; Ozden, Sehmus; Priestley, Rodney; Arnold, Craig; Chopra, Nitin; Tiwary, Chandra Sekhar
Abstract: Since its isolation by Geim and coworkers, graphene has received a lot of attention from the research community as well as industry. Interesting and groundbreaking research has been published on graphene showing excellent properties and a wide range of applications. It was thought that graphene could replace well-established applications currently being controlled by graphite. In this perspective, we review large-scale applications of graphite that we think graphene can replace. We also discuss niche applications that we think graphene can make inroads for large-scale applications.